Impacto de las campañas publicitarias en contra de la piratería de música, implementadas desde el año 2013 en Guayaquil, a los ciudadanos de 20 a 44 años de edad, económicamente activos - Mosquera Ochoa, Cecilia Elizabeth (2016)
The project called “The impact of advertising campaigns against music piracy, implemented since 2013 in Guayaquil to economically active citizens from 20 to 44 years old” has the main purpose to create awareness to the public about importance of the rights author, for people who create or have companies linked to this kind of activity. Unfortunately in Ecuador we have a lot of these piracy cases in all fields; they have generated big losses at national and international level to those engaged in this kind of activity. The deductive method was used in the methodological framework because surveys were applied to people 20 to 44 years old in the Guayaquil city, to determine the impact produced about the publicity campaigns against piracy music, which were conducted from 2013 to 2015 and then analyze if there was a change of attitude was in consumers, the type of research was applied like a social phenomenon advertising campaigns. For its design the research is from field because studies the behavior of the market; with a quantitative approach due to data collection through structuring and implementation of surveys, statistical measurement, to determine the attachment to reality, patterns of behavior in the Guayaquil city through survey application and interviews, which they led to the analysis, conclusions and recommendations of the work…..